Acute scrotum in setting of acute pancreatitis. (17th March 2018) - Sood, Akshay; Cole, Daniel; Alanee, Shaheen
Abstract : Acute scrotum is a urologic emergency with many aetiologies. Acute scrotum in setting of acute pancreatitis is a rare occurrence and results from an effusion of pancreatic juices into the inguinal canal along a retroperitoneal tract. Knowledge regarding the existence of this obscure condition is essential for its diagnosis. It is thus important for medical professionals, particularly internists, surgical trainees and emergency physicians, to be aware of the condition and the options for its management.